Translation Quality of Figurative Languages on School Notice Boards - Nurul Laelatul Padilah (Journal of English Language Teaching and Cultural Studies, 2021)
The objective of research is to figure out different kinds of figurative language in school board notice, to present translation techniques employed in school board notice, and to find out the effects of translation techniques used by the translator on the quality of translation. The researcher used the qualitative research by using content analysis. This study employs three parameters: accuracy, acceptability, and readability. The study covered collecting, analyzing, and interpreting the data of figurative languages types. The noticeboard in school contains figurative languages namely metaphor, idioms, hyperbole, contextual expression. They were found in the noticeboard in school. Based on the analysis, however, there were only twelve techniques namely linguistic compressions, literal translation, adaptation, modulation, linguistic amplification, discursive creation, compensation, transposition, established equivalent, borrowing, generalization, particularization used to translate figurative language utterances in noticeboards at school. The findings show that figurative language found in the translation of noticeboards is contextual expression. It encompasses indexical demonstrative expression. The hidden indexical expression shows environmental report and automatic indexical.